Antisense Oligonucleotide Technologies to Combat Obesity and Fatty Liver Disease - Keating, Michael F.; Drew, Brian G.; Calkin, Anna C. (Frontiers in Physiology, 2022)
Synthetic oligonucleotide technologies are DNA or RNA based molecular compounds that are utilized to disrupt gene transcription or translation in target tissues or cells. Optimally, oligonucleotides are 10–30 base pairs in length, and mediate target gene suppression through directed sequence homology with messenger RNA (mRNA), leading to mRNA degradation. Examples of specific oligonucleotide technologies include antisense oligonucleotides (ASO), short hairpin RNAs (shRNA), and small interfering RNAs (siRNA). In vitro and in vivo studies that model obesity related disorders have demonstrated that oligonucleotide technologies can be implemented to improve the metabolism of cells and tissues, exemplified by improvements in fat utilization and hepatic insulin signaling, respectively. Oligonucleotide therapy has also been associated with reductions in lipid accumulation in both the liver and adipose tissue in models of diet-induced obesity. Recent advances in oligonucleotide technologies include the addition of chemical modifications such as N-acetylgalactosamine (GalNAc) conjugates that have been successful at achieving affinity for the liver, in turn improving specificity, and thus reducing off target effects. However, some challenges are still yet to be overcome relating to hepatic injury and off-target effects that have been reported with some compounds, including ASOs. In summary, oligonucleotide-based therapies are an effective tool to elucidate mechanistic insights into metabolic pathways and provide an attractive avenue for translational research into the clinic.